Was the “ABC” Approach (Abstinence, Being Faithful, Using Condoms) Responsible for Uganda’s Decline in HIV? - Murphy, Elaine M.; Greene, Margaret E.; Mihailovic, Alexandra; Olupot, Peter Olupot (PLoS medicine, 2006)
Uganda is one of the few African countries where rates of HIV infection have fallen, from about 15 percent in the early 1990s to about five percent in 2001. At the end of 2005, UNAIDS estimated that 6.7 percent of adults were infected with the virus. The reasons behind Uganda's success have been intensely studied in the hope that other countries can emulate the strategies that worked. Some researchers credit the success to the Ugandan government's promotion of “ABC behaviors”—particularly abstinence and fidelity. Uganda receives funds from the United States President's Emergency Plan for AIDS Relief, which promotes the ABC approach with a focus on abstinence-driven public health campaigns. Other researchers question whether the ABC approach was really responsible for the decline in HIV infection. Critics of the ABC approach also argue that by emphasizing abstinence over condom use, the approach leaves women at risk of infection, because in many parts of the world women are not empowered to insist on abstinence or fidelity.